Karakteristik morfometrik kerang mutiara Pinctada margaritifera di Perairan Arakan, Mantehage Bango dan Talengen Provinsi Sulawesi Utara untuk kelayakan budidaya - Silalahi, Torang J. P.; Kalesaran, Ockstan J.; Lumenta, Cyska; Mingkid, Winda M.; Ngangi, Edwin L. A. (e-Journal BUDIDAYA PERAIRAN, 2022)
The purpose of this study were (1) to determine the morphometric characteristic of pearl oyster Pinctada margaritifera in Arakan, Mantehage Bango, and Talengen waters of North Sulawesi Province, (2) to determine the ideal location for the feasibility of pearl oyster culture. Determination of the sampling location is done by purposive sampling. The shell morphometric dimensions measured were shell length, shell height, hinge length, shell thickness and shell weight. The measured water quality were temperature, salinity, dissolved oxygen, pH, and depth. The morphometric characteristic of P. margaritifera oyster in Arakan waters have shell length (PC) ranging from 44,25 – 169,77 mm with an average of 86,50 mm, Mantehage Bango waters have PC ranged from 38,73 – 106,09 mm with an average of 80,31 mm, and Talengen waters have PC ranged from 25,89 mm to 105,34 mm with an average of 68,97 mm. Arakan waters are dominated by medium size P. margaritifera (53,78%), it is suspected that Arakan waters have pearl oyster stocks in nature for aquaculture activities. Evaluation of the suitability of waters for pearl oyster culture P. margaritifera in Arakan waters scored 77,7% categorized as suitable (S2), the location of Mantehage Bango waters scored 80% categorized as suitable (S2) and the location of Talengen waters 68,8% categorized as conditional (S3).